The Problematics of Iran's Retaliatory Attack on Israel: Evaluation of the Principles of Necessity and Proportionality Based on Article 51 of the UN Charter. - Irvan, Mohammad; Sutrisno, Andri; Ode, Afrizal (IAIN Bone, 2024)
This research analyses the legitimacy of the Islamic Republic of Iran's retaliatory strike against Israel on 1 April 2024 in the context of Article 51 of the United Nations Charter, focusing on the application of the principles of necessity and proportionality in international law. The research method used is descriptive-analytical with a normative approach, where international legal norms and the doctrine of self-defence are analysed to assess the validity of Iran's actions. The results of the analysis show that the claim of self-defence by Iran raises doubts, especially in relation to the principle of necessity, given the 11-day time lag between Israel's initial attack and Iran's retaliation, which may not fully meet the immediacy standard. In addition, the scale of Iran's counter-attack, which involved over 300 drones and missiles, appears disproportionate to the threat faced, raising questions regarding compliance with the principle of proportionality. The implications of these findings point to the need for further affirmation of international legal standards regarding self-defence and an enhanced role for the UN Security Council in overseeing such actions to maintain international peace and security.